Advances in biotechnology and clinical therapy in the field of peripheral nerve regeneration based on magnetism - Fan, Zheyuan; Wen, Xinggui; Ding, Xiangdong; Wang, Qianqian; Wang, Shoushuai; Yu, Wei (Frontiers in Neurology, 2023)
Peripheral nerve injury (PNI) is one of the most common neurological diseases. Recent studies on nerve cells have provided new ideas for the regeneration of peripheral nerves and treatment of physical trauma or degenerative disease-induced loss of sensory and motor neuron functions. Accumulating evidence suggested that magnetic fields might have a significant impact on the growth of nerve cells. Studies have investigated different magnetic field properties (static or pulsed magnetic field) and intensities, various magnetic nanoparticle-encapsulating cytokines based on superparamagnetism, magnetically functionalized nanofibers, and their relevant mechanisms and clinical applications. This review provides an overview of these aspects as well as their future developmental prospects in related fields.